The Impact of Autonomy and Decision Making on the Morale and Motivation of Technical Vocational Education and Training (TVET) Lecturers in the Eastern Cape, South Africa - Nikisi, Ernest; Mashologu, Mabel Wendy; Bwowe, Patrick W.; Masha, Anthony Kambi (Research in Social Sciences and Technology, 2025)
The study focused on the impact of autonomy and decision making on the morale and motivation of TVET college lecturers in the Eastern Cape Province of South Africa. The study also exposed the autonomy and decision-making factors affecting the lecturers and it gave possible ways to minimise the negative impact on the teaching and learning programmes of the colleges. The research sample comprised of 40 female and male participants whose ages ranged from 25 to 60 years and were drawn from two randomly selected colleges. The study followed a mixed methods approach where both questionnaire and interview instruments were used to collect data giving rise to both qualitative and quantitative data respectively. The findings uncovered that autonomy and decision making among lecturers is negatively affecting lecturers’ morale and motivation. Factors that are making autonomy and decision-making problematic include participation prohibition, leadership restrictions and reduced self-reliance at work.